BLOG-GOTHIC AS AN INTERACTIVE LEARNING MEDIA IN ANALYTICAL GEOMETRY COURSE - Rohmah Indahwati; Chairul Fajar Tafrilyanto (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to determine (1) how the application of Blog-Gothic as an interactive learning media in Analytical Geometry course (2) the response of students to the use of Blog-Gothic as an interactive learning media in the course of Analytical Geometry. This blog utilization is expected to produce a significant influence, which is in addition to aiming to improve student learning outcomes, it is also expected to help students wisely utilize the internet to find material lectures, discuss difficulties in certain subjects and increase creativity in writing. In addition, lecturers are also easier to monitor the progress of their students through their Blogs or by visiting student Blogs. It is also expected to be able to overcome the diversity of the ability to ask and argue and also can be a solution to the lack of face-to-face hours of lectures. This research is a quantitative research with the use of quasi-experimental or quasi-experimental. Subjects are given an initial test and then given Blog-based learning and then given a final test to find out the improvement in learning outcomes. Observations, questionnaires and interviews were conducted to obtain student response data on Blog-Gothic usage.